INTERVENTION STRATEGY FOR COMMUNITY EMPOWERMENT IN THE 3T REGION THROUGH THE FIVE MAIN OUTCOME AREAS (5 BHP) METHOD: STRATEGI INTERVENSI PEMBERDAYAAN MASYARAKAT WILAYAH 3T MELALUI METODE LIMA BIDANG HASIL POKOK (5 BHP) - Sania Fitri; Isbandi Rukminto Adi (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2025)
The Village Potential Economic Empowerment Program in the Agriculture and Livestock Sector in Bukit Permata Village, East Kutai Regency faces complex challenges as a frontier, outermost, and underdeveloped area with infrastructure limitations, geographical isolation, and low human resource quality. This study aims to analyze the intervention strategy of PT Bina Swadaya Konsultan in empowering the local community in Bukit Permata Village through PT I's Corporate Social Responsibility program. The method uses descriptive qualitative with data collection techniques through in-depth interviews and observations of program implementers and assisted groups. The results of this study indicate that the intervention strategy using the Five Main Result Fields method consisting of strengthening organizational, administrative, capital, productive business, and acceptance aspects has been successfully implemented systematically. The strategy begins by building trust through live-in approaches, door-to-door visits, and participation in community activities. The formation of Community Self-Help Groups becomes an effective forum for collective learning and developing productive businesses that provide real economic benefits to members.